Supervision, Axis of Change in Educational Systems - Mª Antonia Casanova (Universidad Autónoma de Madrid, 2015)
The author makes a review through the ordinary tasks of the Inspectorate of Education, which she focuses in giving information and advice, mediating, checking and evaluating, and she summarizes all this tasks under the name of educational supervision, making synonymous supervision with inspection. She regards supervision as a link between the educational administration and the school, basing the achievement of suitable response of the educational system to the demands of society on the grounds of an agile and proper way of working of schools. Among the tasks analyzed, she considers control and evaluation as the specific tasks, which guarantee the right of children to a high quality type of education and the possibility of improving the educational system as a whole. It finally considers that inspection must endorse the educational quality of the system together with the direction of the centers, especially in situations of change, innovation and reform.